Rafflesia tunku-azizahiae (Rafflesiaceae), a new species from Pahang, Malaysia - Jumaat H. Adam,; Mohd. Afiq Aizat-Juhari,; Nik Nadira-Farhana Nik Ariff,; Shamsul Khamis,; Mohd. Hizamri Mohd. Yasin,; Wan, Kiew-Lian (Universiti Kebangsaan Malaysia, 2022)
A new species of Rafflesia (Rafflesiaceae) from Mt. Benom Forest Reserve, Ulu Dong, Raub, Pahang, Rafflesia tunku-azizahiae Adam, Aizat-Juhari & Wan is described and illustrated. Cluster analysis and principal component analysis showed that R. tunku-azizahiae and R. tuanku-halimii are closely related morphologically, characterized by perigone lobes covered by rows of very closely spaced coalesced white warts, and windows wholly covered by very closely rings of coalesced white warts. Score plot and bi-plot showed that R. tunku-azizahiae differs from R. tuanku-halimii by larger flower diameter, broader diaphragm and disc diameter, larger aperture diameter and longer ramenta.